WORKING CONDITIONS AND GIG WORKERS’ PARTICIPATION: THE ROLE OF EMPLOYMENT STATUS AND LITERACY - Wibowo, Wibowo; Kodrat, David (Jurnal Riset Bisnis dan Manajemen, 2026)
This study examines how working conditions influence gig workers’ participation in employment social security programs. Using a quantitative explanatory survey, it analyzes the effects of income level, working hours, and order stability on participation, with employment relationship status as a mediating variable and financial literacy and social security literacy as moderating variables. Data were collected from 300 gig workers engaged in ride-hailing, food delivery, and logistics platforms through purposive sampling. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used to test direct, indirect, and moderating effects simultaneously. The findings show that income, working hours, and order stability significantly affect employment relationship status, which in turn positively influences social security participation. Financial literacy strengthens this relationship, whereas social security literacy does not show a moderating effect. Overall, the results highlight the importance of employment clarity and financial capability in expanding gig workers’ social protection inclusion.